Business intelligence: visualização de dados a partir do enfoque narrativo - Oliveira, Ricardo Lemos (2020)
The speed with which the data is being generated has been increasing significantly, and is driven by an economic dispute where having information becomes a competitive advantage over the competition. It turns out that making relevant information available to users is one of the challenges of business intelligence. From images that allow the visualization of the information, the transformation of the data into interpretative possibilities is observed, where the user is able to analyze and extract useful information. The use of narratives has also been explored for the presentation of large volumes of data, due to their ability to give context to the information represented. Therefore, the purpose of this research is to analyze and propose ways of presenting data, through narrative forms in the business context, in order to support decision making in a corporate environment, based on the creation of a data visualization model. . With the proposed model and from the result of analysis, it is believed that the present work can support the construction of narratives, ranging from the mapping of narrative elements, to visual representation